Effects of Panax notoginseng ginsenoside Rb1 on abnormal hippocampal microenvironment in rats. (18th April 2017) - Wang, Shiyun; Li, Minghong; Guo, Ying; Li, Chen; Wu, Lanou; Zhou, Xin-Fu; Luo, Yaohui; An, Dong; Li, Shude; Luo, Haiyun; Pu, Lijin
Abstract: Cerebral ischemia damages central neurons, and abnormal microenvironment in ischemic condition is the key factor to the damages. The increase of local concentration of glutamic acid, the overload of Ca 2+, and the mitochondrial stress caused by release of cytochrome C are important factors of abnormal microenvironment in cerebral ischemia. In this study ginsenoside Rb1, a compound from Panax Notoginseng, was used to intervene abnormal environment of neurons in the hippocampal CA1 region in two animal models (microperfusion model and photothrombosis model). Results: Compared with the vehicle in the sham group, ginsenoside had following effects. a) ginsenoside Rb1 increased the regional cerebral blood flow (rCBF) and the stability of neuronal ultrastructure in in the hippocampal CA1 region and improved the adaptability of neurons in two models. b) ginsenoside Rb1 improved the expression level of glial glutamate transporter1 (GLT-1) and reversed the uptake of glutamate (Glu) after ischemia, and as a result thereby decreased the excitability of Glu and the expression level of GLT-1 was proportional to the dose of ginsenoside Rb1 and similar to that of Nimodipine. c) ginsenoside Rb1 inhibited the expression level of NMDAR and the overload of Ca 2+, thereby reducing neuronal damages. Meanwhile, the expression level of NMDAR was inversely proportional to the dose of ginsenoside Rb1, which was similar to that of Nimodipine. d) ginsenoside Rb1 decreased the release of cytochrome C (Cyt-C) and reduced the damages caused by neuronal mitochondrial stress. Meanwhile, the release of Cyt-C was inversely proportional to the dose of ginsenoside Rb1, which was similar to that of Nimodipine. Ginsenoside Rb1 may be as an effective drug for neuroprotection and improve cerebral blood flow after acute ischemia and prevent the secondary brain damage induced by stroke.